Collaboration of Educational Actors in Formulating Integrated Curriculum Based on Islamic Values in Aceh - Nur Hafni; Aiyub Aiyub (Master Program of Sociology, Universitas Malikussaleh,, 2021)
The Province of Aceh has a robust legal basis and umbrella in implementing an education system based on Islamic values following the mandate of Law No. 11 of 2006 and is described in the provincial and district qanuns of North Aceh. Implementing the special autonomy policy in education gives the Aceh Provincial government the flexibility to develop creative and innovative Islamic-based programs following the characteristics of Aceh's privileges. This study aims to analyze the formulation of Islamic values-based curriculum education policies in primary education and the collaborative actors involved in forming Islamic values-based educational curriculum policies. The research was used the descriptive qualitative method. The informants were determined by purposive sampling. The study found no synergy of cross-actor in collaborative governance in the formulation of Islamic values-based Aceh education curriculum policies. Thus, the implementation of education programs based on Islamic values was interpreted and meant differently among agencies. In addition, the National Curriculum strongly dominated the implementation of Aceh education in primary education, while local policies on Islamic values were few. Therefore, the policies of providing education do not reflect the specificity of Aceh's privileges. Besides that, the Islamic-based education policy program was not explained in a more detailed derivative policy.